RETROSPECTIVE STUDY REGARDING LYMPHOMAS OF THE PAROTID GLAND - Andrei Nicolau; Constantin Mihai; Otilia Boișteanu; Doriana Forna; Eugenia Popescu (Romanian Society of Oral Rehabilitation, 2015)
Aim of the study Carrying out a clinical statistical study of patients diagnosed with parotid lymphomas in the Oral and Maxillofacial Surgery Clinic of Iasi with a view to improving the methods of early diagnosis and establishing the best therapeutic indication. Material and methods The study was carried out on a number of 56 patients diagnosed with parotid lymphomas and surgically treated in the period 1950-2013. The study relied on all the data registered for each patient in the observation charts and in the anatomo-pathological bulletins, focusing on the information about the histopathological form of the lymphoma, its location, the surgical intervention applied and the post-operative sequelae. Results Parotid gland lymphomas represent about 5% of all parotid tumors and 13% of the malignant ones. 80% were non-Hodgkin lymphomas. The highest incidence was found in the age decades 31-40 and 41-50, predominantly in males. 80% of the parotid lymphomas were on the superficial lobe. In most cases, the facial nerve was preserved. Conclusions The anatomical particularities and the increased quantity of tumoral tissue necessary for the anatomo-pathological examination require the removal of the tumor by parotidectomy in the cases when there was only one tumoral location at the level of the parotid gland.